NAPOLO AND OTHER POEMS - Chimombo, Steve Bernard Miles (Book collections on Project MUSE., 2021)
This collection of verse contains poems from Malawi's foremost writer, most of which were written in the 1970s. Poet, fiction writer, playwright, and children's author Steve Bernard Miles Chimombo was born in Zomba, Malawi, and educated at the University of Malawi, the University of Wales, the University of Leeds, and Columbia University. Mythology and oral culture inform his poetry, and he frequently used both modernist techniques and wry humor to address political themes.